Efficient simulated annealing based solution approaches to the competitive single and multiple allocation hub location problems. (February 2018) - Ghaffarinasab, Nader; Motallebzadeh, Alireza; Jabarzadeh, Younis; Kara, Bahar Y.
Highlights: Competitive single and multiple allocation hub location problems are addressed. New MIP models are proposed for the leader and follower under both allocation schemes. Efficient simulated annealing (SA) heuristics are proposed for solving the problems. Problem is extended to accommodate more general capture mechanisms. Extensive computational experiments are conducted for the considered problems. Abstract: Hub location problems (HLPs) constitute an important class of problems in logistics with numerous applications in passenger/cargo transportation, postal services, telecommunications, etc. This paper addresses the competitive single and multiple allocation HLPs where the market is assumed to be a duopoly. Two firms (decision makers) sequentially decide on the configuration of their hub networks trying to maximize their own market shares. The customers choose one firm based on the cost of service provided by these firms. Mathematical formulations are presented for the problems of the first and second firms (the leader and the follower, respectively) and Simulated Annealing (SA) based solution algorithms are proposed for solving these problems both in single and multiple allocation settings. Extensive computational experiments show the capability of the proposed solution algorithms to obtain the optimal solutions in short computational times. Some managerial insights are also derived based on the obtained results.